Al-jabiri's traces in m. amin abdullah's idea about integrative-interconnective paradigm for higher education - Syamsul Kurniawan (IAIN Salatiga, 2020)
Between Islamic science and science, according to M. Amin Abdullah, it should not be dichotomous and lack a strong epistemological basis. For this purpose, the work of